2011
DOI: 10.1172/jci45961
|View full text |Cite
|
Sign up to set email alerts
|

The three R’s of lung health and disease: repair, remodeling, and regeneration

Abstract: All tissues and organs can be classified according to their ability to repair and regenerate during adult homeostasis and after injury. Some exhibit a high rate of constant cell turnover, while others, such as the lung, exhibit only low-level cell regeneration during normal adult homeostasis but have the ability to rapidly regenerate new cells after injury. Lung regeneration likely involves both activation of progenitor cells as well as cell replacement through proliferation of remaining undamaged cells. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
243
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(249 citation statements)
references
References 94 publications
4
243
0
2
Order By: Relevance
“…81 The functions of these genes and the effects of their risk-associated polymorphisms have drawn attention to the endoplasmic reticulum stress response, resilience, survival, and replenishment of lung epithelial cells. 15,75 Moreover, these connections between epithelial cell death and lung fibrosis help justify the continued and widespread use of lung epithelial injury by bleomcyin to cause fibrosis, despite this model's acknowledged flaws. 82 A strengthening hypothesis to generally explain fibrotic lung diseases is that injury or infection overcomes an already stressed epithelium's capacity for recuperation and engages innate immune pathways that may circumstantially promote or protect from harm.…”
Section: Myofibroblasts In Lung Fibrosis and Degenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…81 The functions of these genes and the effects of their risk-associated polymorphisms have drawn attention to the endoplasmic reticulum stress response, resilience, survival, and replenishment of lung epithelial cells. 15,75 Moreover, these connections between epithelial cell death and lung fibrosis help justify the continued and widespread use of lung epithelial injury by bleomcyin to cause fibrosis, despite this model's acknowledged flaws. 82 A strengthening hypothesis to generally explain fibrotic lung diseases is that injury or infection overcomes an already stressed epithelium's capacity for recuperation and engages innate immune pathways that may circumstantially promote or protect from harm.…”
Section: Myofibroblasts In Lung Fibrosis and Degenerationmentioning
confidence: 99%
“…82 A strengthening hypothesis to generally explain fibrotic lung diseases is that injury or infection overcomes an already stressed epithelium's capacity for recuperation and engages innate immune pathways that may circumstantially promote or protect from harm. 13,15,53,64,75,78,81 Myofibroblasts are the key effector cell type in fibrotic disease because they are dominant builders and remodelers of extracellular matrix that also exert strong force on their surroundings. 9,10,12e14,27,30,38,53,64,78,83 Myofibroblasts may be distinguished by expressing a-SMA and similar proteins in common with muscle, forming stress fibers, and by contractility.…”
Section: Myofibroblasts In Lung Fibrosis and Degenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…The coordinating interactions in forming, maintaining and repairing such an organ are therefore numerous and complicated. Subsequent research has shown that these interactions are mediated by contextdependant signaling mechanisms that are spatially and temporally precise and specific [17]. Expression of a particular mediator in a slightly inaccurate location or time can result in biochemical or structural defects and this applies to many different organ systems [18].…”
Section: I) Embryological Organ Formationmentioning
confidence: 99%